Conservatives and the Constitution : imagining constitutional restoration in the heyday of American liberalism / Ken I. Kersch. - Kersch, Kenneth Ira, 1964- (Cambridge studies on the American Constitution., 2019)
Since the 1980s, a ritualized opposition in legal thought between a conservative 'originalism' and a liberal 'living constitutionalism' has obscured the aggressively contested tradition committed to, and mobilization of arguments for, constitutional restoration and redemption within the broader postwar American conservative movement. Conservatives and the Constitution is the first history of the political and intellectual trajectory of this foundational tradition and mobilization. By looking at the deep stories told either by identity groups or about what conservatives took to be flashpoint topics in the postwar period, Ken I. Kersch seeks to capture the developmental and integrative nature of postwar constitutional conservatism, challenging conservatives and liberals alike to more clearly see and understand both themselves and their presumed political and constitutional opposition. Conservatives and the Constitution makes a unique contribution to our understanding of modern American conservatism, and to the constitutional thought that has, in critical ways, informed and defined it.